Backache and Dentistry A survey in Baghdad - Iraq - Mohammed S Al-Casey; Raid F Al-Huwaizi; Akram F Al-Huwaizi
A questionnaire was given to each of 242 dentists working in the city of Baghdad, of whom 150 were males and 92 were females. Back pain was reported by 125 dentists (51.7%), more frequently in the lumber area (48%). No statistically significant sex differences were found, while back pain tended to increase with age especially in the cervical area. Significant associations were found between back pain and sitting down working position and the number of patients the dentist treats per day.